1984
DOI: 10.1177/002199838401800203
|View full text |Cite
|
Sign up to set email alerts
|

Orthotropic Thermoelastic Problem of Uniform Heat Flow Disturbed by a Central Crack

Abstract: The linear thermoelastic problem of uniform heat flow disturbed by a central crack in an orthotropic plate is investigated using the techniques of Fourier Transforms and multiple integrations. The thermoelastic stresses and displacements in the crack plane are obtained in closed forms. The stress intensity factor is presented as a function of the material properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 4 publications
0
23
1
Order By: Relevance
“…Chen [4] used a piezoelectric material to adjust the stiffness of the wires to control the response of a structure. Chen, Fanson, Caughey, Hanagud and Baily initiated experimental and theoretical research on smart beam type structures with piezoceramics as integral sensors and actuators [5][6][7][8][9]. Crawley showed that piezoceramic patches can be embedded in composite laminates to control a precision structure [10, 11].…”
Section: Smart Materials and Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen [4] used a piezoelectric material to adjust the stiffness of the wires to control the response of a structure. Chen, Fanson, Caughey, Hanagud and Baily initiated experimental and theoretical research on smart beam type structures with piezoceramics as integral sensors and actuators [5][6][7][8][9]. Crawley showed that piezoceramic patches can be embedded in composite laminates to control a precision structure [10, 11].…”
Section: Smart Materials and Structuresmentioning
confidence: 99%
“…Readers interested in this area may refer to books by Nye [8], Berlincourt et.al. [9], and Landau and Lifshitz [10]. A phenomenological description of the dynamic response of piezoceramics to an external electric field, including domain reorientation processes and the dynamics of dipole moment in each domain, has been developed by Chen et.al.…”
Section: Nonlinear Constitutive Relations For Piezoceramicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the singularity of the stress fields near the crack-tip with a specified temperature or heat flux loading is studied by Sih [6]. The stress intensity factors of a central crack in an orthotropic material under a uniform heat flow are given by Tsai [7]. The thermoelasticity problem of two collinear cracks embedded in an orthotropic solid has been considered by Chen and Zhang [8].…”
Section: Introductionmentioning
confidence: 99%